Shifting geographies of legal cannabis production in California. (June 2021) - Dillis, Christopher; Biber, Eric; Bodwitch, Hekia; Butsic, Van; Carah, Jennifer; Parker-Shames, Phoebe; Polson, Michael; Grantham, Theodore
Abstract: The cannabis industry in California is attempting to transition from an international epicenter of unpermitted production to one of the world's largest legal markets. This formalization process will likely establish new centers of production outside the state's historical cannabis-producing regions, with implications for local communities and the environment. In this paper we analyzed how cultivation regulations and land characteristics correlate with the geographical development of permitted cannabis production centers in California. We used permit data from the first two years of California's statewide cannabis regulatory program to document geographic variation in cannabis production and farm characteristics (prevalence of onsite residence, non-landowner farming, county zoning classifications, size of cultivation area). We also used multilevel regression models to analyze whether geospatial characteristics likely to be relevant to environmental regulations (size of parcel, average slope of parcel, density of stream network, land cover type) were associated with farm size (cultivation area) or the likelihood of a parcel being enrolled in the state program. We found that a small number of large farms represented the majority of the permitted cultivation area, with the top 10% of largest farms comprising 60% of total cultivated area statewide. The counties with the most growth in permitted cannabis cultivation area also had the highest rates of tenant (non-landowner) farming and lowest proportions of farms with permanent onsite residency. Farms in these counties were almost exclusively sited on parcels zoned for agriculture. On a statewide scale, parcel size was a reliably positive predictor of enrollment, while average slope and stream network density had reliably negative effects. The same relationships held in predicting cultivation area, together suggesting that the development of the newly-formalized cannabis industry in California may be responsive to environmental regulation. Our results suggest two divergent paths of industry development: one in which smaller farms, which often pre-date legalization, navigate regulations in more remote and rugged regions and a second comprising large farms, which are often newer and operate in areas more favorable to meeting environmental requirements of state and county policies. Highlights: Cannabis production in California is formalizing under a new regulatory framework. Farm sizes and characteristics are changing relative to historical production models. Geography of legal cannabis production may be responsive to environmental policy. Formalization has created two divergent models of cannabis farming in California.